Linking remote sensing, in situ and laboratory spectroscopy for a Ryugu analog meteorite sample - Maturilli, Alessandro; Schwinger, Sabrina; Bonato, Enrica; Helbert, Jörn; Baqué, Mickael; Hamm, Maximilian; Alemanno, Giulia; D’Amore, Mario (Frontiers in Space Technologies, 2022)
In 2022 JAXA issued an Announcement of Opportunity (AO) for receiving Hayabusa2 samples returned to Earth. We responded to the AO submitting a proposal based on using a multi-prong approach to achieve two main goals. The first goal is to address the subdued contrast of remote-sensing observations compared to measurements performed under laboratory conditions on analog materials. For this we will link the hyperspectral and imaging data collected from the spacecraft and the in-situ observations from the MASCOT lander instruments (MARA and MASCam) with laboratory-based measurements of Hayabusa2 samples using bi-directional reflectance spectroscopy under simulated asteroid surface conditions from UV to MIR/FIR achieved using three Bruker Vertex 80V spectrometer in the Planetary Spectroscopy Laboratory. The second goal is the investigation of the mineralogy and organic matter of the samples collected by Hayabusa2, to better understanding the evolution of materials characterizing Ryugu and in general of protoplanetary disk and organic matter, investigating the aqueous alteration that took place in the parent body, and comparing the results with data collected from pristine carbonaceous chondrite analog meteorites. Spectral data will be complemented by Raman spectroscopy under simulated asteroid surface conditions. X-ray diffraction, would also allow us to define the bulk mineralogy of the samples as well as investigate the presence and nature of organic matter within the samples. In situ mineralogical and geochemical characterization will involve a pre-characterization of the sample fragments through scanning electron microscopy (SEM), low voltage electron dispersive X-ray (EDX) maps, and micro IR analyses of the fragments. If allowed, a thin section of one grain will be used for electron microprobe analyses (EMPA) to geochemically characterize its mineralogical composition. To train our data collection and analysis methods on a realistic sample, we selected a piece of the Mukundpura meteorite, as one of the closer analogs to Ryugu surface, with 3mm in its maximum dimension, to have a test sample of the same size as the Hayabusa2 grain we have been asking in our proposal to JAXA’s AO. The test gave us confidence that we can measure with good SNR measurements in bi-directional reflectance for samples around this size.